Biodiesel production from new algal sources using response surface methodology and microwave application - Hasnain, Maria; Abideen, Zainul; Naz, Shagufta; Roessner, Ute; Munir, Neelma (Biomass conversion and biorefinery, 2023)
Society is looking for clean alternate fuels due to the increased depletion of fossil fuels and energy demands. The cost of oil extraction and downstream biodiesel conversation processes are the main limiting factor to commercialized algal biodiesel. The effect of microwave irradiation on the simultaneous in situ transesterification and extraction of algae lipids was investigated for biodiesel production. The response surface methodology (RSM) with the central composite design was used to analyze catalyst concentration and reaction time. Oedogonium sp., Ulothrix sp., Cladophora sp., and Spirogyra sp. were collected and treated with microwave techniques with different optimized conditions by RSM. Results indicated that microwave technique enhanced biodiesel production in 73%, 88%, 80%, and 67% from Oedogonium sp., Ulothrix sp., Cladophora sp., and Spirogyra sp. dry weight (DW), respectively, with 1 wt.% catalyst concentration (potassium hydroxide) and 3 min with constant methanol concentration. Catalyst concentrations of up to 0.5 wt.% showed a positive effect on the transesterification reaction. The reaction time has a significant effect on biodiesel production. Under microwave irradiation, 3–6-min reaction time seems suitable for the complete in situ transesterification reaction. Microwave heating transesterification has been shown to be more effective for adequate biodiesel yield compared to the conventional transesterification process. This study suggested that Ulothrix sp. qualify as the most efficient feedstock for biodiesel production and that microwave-assisted in situ transesterification eliminates the need for high quantity of solvents, longer reaction times, and high reaction temperatures and pressures.